Analisis Keputusan Nasabah Dalam Menabung(Pendekatan Model Logistik Studi pada Bank Syariah di Kota Surakarta) - Suryanda, Aldian; , M. Sholahuddin, SE., M.Si (2016)
The election was client decision in saving at sharia bank giving facility to client. Many factors influencing it like client enthusiasm, services quality, bank characteristic, client knowledge, and quality of product. This research purpose to identifying factors client decision influencing in saving by logistic regression model approach at sharia bank in Surakarta City. This research represent quantitative research with 100 people as sample by accidental sampling, where was 50 people represent the client of sharia bank and 50 people represent the client of conventional bank. The data collecting technique was using questioner with likert scale. The data technique analyze was using logistic regression inferential analysis. Pursuant to result analyse known that the majority of men client, 31 - 40 years old, and working as entrepreneur. Logistic regression analysis result known that client enthusiasm, quality of service, bank characteristic, client knowledge, and quality of product have an effect on client decision in saving especially in Sharia bank. The variation of client enthusiasm, quality of service, bank characteristic, client knowledge and quality of product variable can be explain the client decision in saving at sharia bank and conventional bank variable equal to 38,2%. Based on logit estimate result can be told that client decision in chosening or not chosen the sharia bank in saving influenced by client enthusiasm, quality of service, bank characteristic, client knowledge and quality of product variable.